New species in Diplusodon (Lythraceae) from Brazil - Cavalcanti, Taciana Barbosa (Phytotaxa, 2015)
Six new Diplusodon species from Brazil are described, illustrated and compared with related species. They include Diplusodon rotatus, a novelty from savannas with rocky soils of Maranhão state, D. stellatus, D. venosus and D. vittatus from the mountains of Goiás state, D. verruculosus from the campos rupestres mountains of Minas Gerais state, and D. xiphodon from campos rupestres mountains of Bahia.